Uma voz feminina na política – o ethos discursivo da presidente (a) Dilma Rousseff - Lo Giudice, Rafael Furlan (2014)
The general objective of this research is to reflect upon some of Dilma Rousseff´s discursive sequences, during the period from 2007 to 2011, by observing the enunciative strategies that construct an enunciator image, a discursive ethos (MAINGUENEAU, 2005), which emphasises the feminine side and the competence of the presidential candidate and then incumbent president Dilma Rousseff, on the basis of a pre-discursive ethos, which reinforced the image of a calculating technocrat or of a leftist militant, a communist, a guerrilla-member. We base our reflection on the premise that, since her pre-candidacy, president Dilma Rousseff has given new contours to the Brazilian political discursive practices in order to create an image, which is based upon the denial of a feminine stereotype that is founded on the woman´s submission, which establishes itself on the presumption of a weakness that would prevent her from performing roles which are considered exclusively masculine. The theoretical and methodological assumptions are those of the Discourse Analysis of French origin. Keywords: Political discourse; Dilma Rousseff; Ethos; Media.